COMPARISON BETWEEN LATHE-CUT AND CAST-MOLDING SOFT CONTACT LENS MANUFACTURING TECHNIQUES ON OCULAR SURFACE INTEGRITY: A DOUBLE-BLIND RANDOMIZED CONTROL TRIAL (Journal of Medical & Health Sciences Review, 2025)
Background:Soft contact lenses are widely used for vision correction due to their comfort and optical performance. The manufacturing technique—whether lathe-cut or cast-molded—can significantly affect lens properties, including surface smoothness, hydration, and oxygen transmissibility. These factors may influence ocular surface health and long-term wearability.Objective: To compare the impact of lathe-cut versus cast-molding soft contact lens manufacturing techniques on ocular surface integrity among first-time lens users.Methods: This double-blind randomized control trial included 70 healthy participants aged 15–35 years with no prior history of contact lens wear, ocular disease, or systemic conditions affecting the eye. This study was conducted in Eye 2 Eye Optometrists, Lahore and ophthalmology department Fuji Foundation hospital Lahore. Participants were randomly assigned to receive either lathe-cut or cast-molded soft contact lenses. Baseline assessments included visual acuity, refractive error, corneal curvature, tear film breakup time (TBUT), Schirmer’s test, and Ocular Surface Disease Index (OSDI) scores. Follow-up evaluations were conducted at 3 and 6 months. Statistical analysis was performed using Chi-square tests and paired t-tests; significance was set at p